2020
DOI: 10.1039/c9nr10145d
|View full text |Cite
|
Sign up to set email alerts
|

Radio- and nano-chemistry of aqueous Ga(iii) ions anchored onto graphene oxide-modified complexes

Abstract: The non-covalent radiolabelling of new graphene oxide-bis(thiosemicarbazonato) nanohybrids with gallium-68 and zirconium-89 ions is reported herein for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…This interaction was shown to be highly favourable with RCYs and stability in human serum (up to 2 h) both 495%. 551 The authors also reported a novel bis(semithiocarbazonate) 68 Ga 3+ complex (Fig. 30C) capable of radiolabelling GO.…”
Section: Radiolabelling Of Organic Nanomaterialsmentioning
confidence: 96%
See 2 more Smart Citations
“…This interaction was shown to be highly favourable with RCYs and stability in human serum (up to 2 h) both 495%. 551 The authors also reported a novel bis(semithiocarbazonate) 68 Ga 3+ complex (Fig. 30C) capable of radiolabelling GO.…”
Section: Radiolabelling Of Organic Nanomaterialsmentioning
confidence: 96%
“…30C) capable of radiolabelling GO. Radiolabelling with this complex allowed high RCY 4 95% and high serum stability 495% up to 2 h. 551 Characterisation using energydispersive X-ray spectroscopy (EDX) mapping the non-radioactive gallium complex suggested that the complex was incorporated non-covalently within the GO layers (Fig. 30C).…”
Section: Radiolabelling Of Organic Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent hydrazinolysis of 2a – c yielded the desired thiosemicarbazides ( 3a – c ). The synthesis of the acenaphthenequinone-based mono(thiosemicarbazone) ligands was achieved following a modification of the previously described methodology, 20 whereby the suspension of acenaphthenequinone and the thiosemicarbazide were reacted in acetic acid under microwave irradiation under a variety of conditions, with the most promising reaction being carried out for 20 min at 90 °C.…”
Section: Resultsmentioning
confidence: 99%
“… 19 There is significant interest in the chemistry of bis(thiosemicarbazone) ligands featuring different radioactive metals as theranostic agents, and their potential as imaging agents for hypoxia has been investigated. 20 The recent developments in the commercial availability of Gallium-68 from 68 Ge/ 68 Ga generators provide a reliable source of this positron-emitting radionuclide. The advantageous decay properties of Gallium-68 ( E max = 1.9 MeV, β + 90%) coupled with a half-life of 68 min make this radionuclide attractive for imaging applications based on small molecules and/or biomolecules with relatively fast uptake and clearance rates.…”
Section: Introductionmentioning
confidence: 99%